Five Roles of the Agricultural Editor in Communications Research - W. L. Carpenter (Journal of Applied Communications, 1978)
There's a place for the practicing agricultural editor in communications research. It may not be a big place, but if you're really interested, you can make a contribution to the field, and probably answer some of the questions about your work that nag you from time to time.